Productive and economic parameters of Isa Brown laying hens in the second production cycle supplemented with non-essential amino acids - Morales, Walter (2018)
The objective of the study was to evaluate productive and economic parameters in Isa Brown laying hens of second cycle supplemented with glutamine + glutamic acid (Aminogut®). Four levels of the commercial product (0, 0.8, 1.6 and 2.4%) were evaluated in diets for second cycle laying hens during thirteen weeks of production (45-119 days). Productive performance data were collected, and economic parameters were evaluated. The supplementation of the ration with Aminogut® at 1.6% improved the number of eggs per housed bird and feed conversion (1.65 kg feed per dozen eggs), although without statistical differences for the variables food consumption, egg size, production of eggs (%) and egg mass. On the other hand, supplementation with Aminogut® during the first two weeks would be a strategy to increase the production of birds and reduce the costs of encasing new lots.